Trust and networking in cross sector collaboration of waqf development and the mediating role of sustainability practices / Siti Sara Ibrahim … [et al.] - Ibrahim, Siti Sara; Mohd Noor, Abd Halim; Ismail, Shafinar; Arshad, Roshayani; Muhamad Don, Mohd Ali (Faculty of Accountancy, 2019)
Cross-sector collaboration in waqf development is an innovative strategy that has received much industry attention. This practice provide a good mechanism for State Islamic Religious Councils (SIRCs), the government as well as public and private sectors in managing and developing waqf properties. The government is also very supportive as it is in line with the national agenda to promote socio-economic growth. This strategy is recognized as the Social Private and Public Partnership or SPPP, which has been initiated by The National Blue Ocean Strategy (NBOS) and incorporated within the 11th Malaysia Plan (RMK-11). However, it should be noted that not all collaborations may result in successful outcomes and contribute to sustainable socioeconomic growth. A successful collaboration is dependent upon the existence and utilization of resources. The management of intangible resources (IRs) is considered as the main factor for successful collaboration practices since IRs are highly innate and non-replicable as well as complementary to the needs of collaborative projects. Accordingly, trust and Networking in Resource-Based View (RBV) as IRs were assessed in this study. A set of questionnaires were distributed to a total number of 160 respondents. The findings of the study showed that trust plays a significant role in the performance of waqf project development in Malaysia between SIRCs and partners. Sustainable practices had confirmed its role as mediating variables in this study thus making the findings more valuable. This study provides insight into the regulator as well as the industry on the critical resources that are needed to efficiently manage collaborative waqf projects with the intention of ensuring socioeconomic growth.